Outcomes and biomarker analyses among patients with COVID-19 treated with interleukin 6 (IL-6) receptor antagonist sarilumab at a single institution in Italy. Issue 2 (11th August 2020) - Montesarchio, Vincenzo; Parella, Roberto; Iommelli, Chiara; Bianco, Antonella; Manzillo, Elio; Fraganza, Fiorentino; Palumbo, Cristiana; Rea, Gaetano; Murino, Patrizia; De Rosa, Rosanna; Atripaldi, Luigi; D'Abbraccio, Maurizio; et al.
Abstract : Background: The inflammatory pathology observed in severe COVID-19 disease caused by the 2019 novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is characterized by elevated serum levels of C reactive protein (CRP) and cytokines, including interferon gamma, interleukin 8 (IL-8), and interleukin 6 (IL-6). Initial reports from the outbreak in Italy, China and the USA have provided anecdotal evidence of improved outcomes with the administration of anti-IL-6 agents, and large-scale trials evaluating these therapies are ongoing. Study description: In this retrospective case series, clinical outcomes and correlates of response to treatment with the IL-6 receptor antagonist sarilumab are described for 15 patients with COVID-19 from a single institution in Southern Italy. Among 10 patients whose symptoms improved after sarilumab treatment, rapid decreases in CRP levels corresponded with clinical improvement. Lower levels of IL-6 at baseline as well as lower neutrophil to lymphocyte ratio as compared with patients whose COVID-19 did not improve with treatment were associated with sarilumab-responsive disease. Conclusions: This observation may reflect a possible clinical benefit regarding early intervention with IL-6-modulatory therapies for COVID-19 and that CRP could be a potential biomarker of response to treatment.